(3GdfXGe GdbGfhfj ddTQcGJ GdeOfjI GdegfjI (B:s (3OQGSI ebGQfI (B= The legal regime for civil professional companies : a comparative study /s - (3YHO GdQTjO, LeGds ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2015)
(3dbO aQV YUQfG GdMOjK fJjLI GdSQYI hGdJbOe GdYdej GdPj fTgOg, ef Gdegf GdMQI GdeSJMOKI eG de JaQVg GdYUhQ GdbOjeI(B. (3hGUWMH Jdc Gdegf UYhHGJ JJQCSgG WQjbI eeGQSJgG GdaQOjI, heG jfJL Yf gPg GdeeGQSI GdaQOjI ef ETcGdjGJ, gPG ef LGfH(B. (3hef LGfH BNQ, aEf GdJbOe hGdJWhQ GdPj jMce GdYGde GdMOjK aQV UYhHGJ Ydi Gdegfjjf PGJge YfO eeGQSJge egfge GdMQI HUhQI aQOjI(B. (3dPG ; haj EWGQ GdSYj ddHMK Yf CfXeI bGfhfjI LOjOI ef TCfgG GdJcGJa hGdJYGVO dehGLgI Jdc GdUYhHGJ, abO ChLOJ CfXeI bGfhfjI eYGUQI JLjR ddegfjjf GdJYGhf hGdJLeY eY HYVge GdHYV HZQV Jchjf TQcI eOfjI egfjI jeGQShf ef NdGdgG fTGWge Gdegfj HUhQI LeGYjI(B. (3aGdfLGMGJ GdJj MbbJgG eNJda GdCYeGd hGdCfTWI GdegfjI GdJj GJNPJ GdTQcI GdeOfjI GdegfjI cEWGQ bGfhfj deeGQSI Jdc GdCYeGd hGdCfTWI, TLY CUMGH Gdegf GdMQI ddJhLg ddeeGQSI GdLeGYjI degfge ef NdGd TQcI eOfjI egfjI, hdYd eG TLY ChdFc Gdegfjjf HRjGOI, Jecf Pdc GdEWGQ GdbGfhfj HehGLgI GdUYhHGJ GdJj aQVJgG GdeJZjQGJ GdafjI hGdGbJUGOjI(B. (3aeKdG ; GdeMGej GdaQO, hCeGe GdJVNe GdJTQjYj GdPj fTgOg Gdjhe, CUHM YGLRG HeaQOg GdEdeGe HTJi GdfUhU GdJj aQVgG Pdc GdJVNe GdJTQjYj(B. (3eeG dG Tc ajg, Cf Pdc GdJWhQ GdJTQjYj Ndb UYhHGJ afjI dOi Pdc Gdegfj GdaQO, JJeKd HYLRg HeaQOg CeGe Pdc GdJWhQ, HGSJYeGd Ch JhXja WQb GdeeGQSI Ch hSGFdgG, YfO eeGQSJg egfI GdeMGeGI(B. (3eeG MPG Hg eLHQG ddJNUU aj CMO aQhY GdbGfhf(B. (3hSGgeJ Jdc GdUYhHGJ GdafjI HUhQI JHYjI hHTcd hGVM aj GdYdGbI eG Hjf Pdc Gdegfj hYejdg, Cj Cf Jdc GdUYhHGJ NdbJ UYhHGJ GbJUGOjI dGMbI dgG(B.s
(3GdCUd QSGdI eGLSJjQ LGeYI GdjQehc(B.s
(3HHdjhLQGajI (B: (3UaMI (B309-319.s
Keywords: (3GdTQcGJs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs; (3Gdegfs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs